Proposal of New Auxological Standards for Japanese Girls with Turner Syndrome - Naiki, Yasuhiro; Ito, Junko; Tanaka, Toshiaki; Yokoya, Susumu; Horikawa, Reiko; Isojima, Tsuyoshi (Clinical Pediatric Endocrinology, 2010)
We recently published new reference growth charts for Japanese girls with Turner syndrome (TS) based on the cross-sectional data of 1,447 subjects beyond the secular trend of growth in Japan. This study was undertaken for their validation and, if necessary, modification before general application. For validation, 24 subjects who had data both at younger (≤5 yr) and older ages (≥13 yr) were used. We analyzed the concordance/discordance of their height standard deviation score (SDS) defined by the charts between the two age periods. For modification, the LMS method was used with 5,772 longitudinal measurements obtained both from the previously analyzed subjects and 118 newly recruited subjects who had been followed up at the National Center for Child Health and Development or Toranomon Hospital. Significant and critical discordance (mean difference, 1.95 SDS; 95% confidence interval (CI), 1.53–2.36; p<0.0001) was detected in height SDS. This prompted us to perform the modifications. A similar analysis using the modified charts revealed no significant discordance (mean difference, 0.27 SDS; 95%CI: –0.17 – 0.71; p=0.22). They seem more adequate for clinical applications for girls with TS born after 1970. New auxological standards for Japanese girls with TS were proposed.